Biological treatment of selenate-containing saline wastewater by activated sludge under oxygen-limiting conditions. (1st May 2019) - Zhang, Yuanyuan; Kuroda, Masashi; Arai, Shunsuke; Kato, Fumitaka; Inoue, Daisuke; Ike, Michihiko
Abstract: Selenium often coincides with high salinity in certain industrial wastewaters, which can be a limitation in the practical application of biological treatment. However, there are no studies on the biological treatment of selenate-containing saline wastewater. A sequencing batch reactor inoculated with activated sludge was applied to treat selenate in the presence of 3% (w/v) NaCl. Start-up of the sequencing batch reactor with a 7-day cycle duration and excessive acetate as the sole carbon source succeeded in removing above 98% and 72% soluble and solid selenium, respectively, under oxygen-limiting conditions. Further selenium removal experiments with a shorter cycle duration of 3 days and a stepwise decrease of acetate addition achieved soluble and total selenium removal efficiencies in most batches above 96% and 80%, respectively. Mass balance analysis revealed that selenate was converted into elemental selenium, most of which was accumulated in the sludge. Microscopic analyses also found that elemental selenium particles were primarily present as approximately 2 μm large rods, with some extremely large particles above 10 μm. Although the bacterial populations responsible for selenium removal, especially selenate reduction, could not be identified by microbial community analysis, this study reported for the first time that selenate could be biologically treated in the presence of considerable salinity, offering implications for the practical treatment of selenium in certain industrial wastewaters. Graphical abstract: Image 1 Highlights: First report on successful biological treatment of selenate in saline wastewater. Selenate (1 mM) can be stably removed within 3 d under oxygen-limiting conditions. Selenate was converted primarily to elemental selenium by bioreduction. Elemental selenium particles primarily accumulated in sludge as large rods.